Assistive Care Robots and Older Adults: Employing a Care Ethics Lens - Hewitt, Rachel (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
To date, ethical critiques of the use of assistive healthcare robotics have not closely examined the purported care relationship between such robots and their users. Drawing upon the work of care ethics scholars, I argue that authentic care relies upon capacities inherently reciprocal and responsive in nature, which ultimately precludes socially assistive robots from being useful caring tools.